Ứng dụng công nghệ và học liệu số trong giáo dục trẻ rối loạn phổ tự kỉ: Tổng quan nghiên cứu và ứng dụng tại Việt Nam - Nguyễn, Hoa; Trần Thị Minh Thành, Trần Thị Minh Thành (Tạp chí Giáo dục, 2026)
The application of technology and digital learning materials is a key trend for enhancing the quality of education for children with autism spectrum disorder. However, implementation effectiveness in developing countries, such as Vietnam, remains limited due to un-synchronized infrastructure, teacher competencies, and learning materials. This study conducted a structured literature review, collecting and analyzing experimental and review studies. A total of 10 studies were selected to evaluate the effectiveness, trends, and influencing factors. The analysis indicates that assistive technologies, such as Augmentative and Alternative Communication (AAC) systems, mobile applications, virtual reality, and interactive learning materials, initially contribute positively to improving children’s skills (Odom et al., 2015; Maskey et al., 2014). Their effectiveness depends on implementation strategies, the degree of personalization, and teacher competence, while being further influenced by infrastructure conditions and the quality of learning materials. The study contributes to systematizing the scientific basis and proposes strategies to promote the application of technology and digital learning materials in education for children with ASD in Vietnam at three levels: (1) Teachers and schools; (2) Training institutions and professional development; (3) Educational management and learning material development. Future research should conduct large-scale and longitudinal experimental studies in the Vietnamese context to validate and refine technology application models in ASD education.